On the Ecology and Silviculture of Dendrocalamus strictus in the Bamboo Forests of Bhadravati Division, Mysore State, and Comparative Notes on the Species Bambusa arundinacea, Oxytenanthera monostigma and Oxytenanthera stocksu - Kadambi, K. (Indian Forester, 1949)
No abstract